PENUNJUK ARAH ABSOLUT DALAM BAHASA TONTEMBOAN - Robot, Kevin Yeremia (Universitas Sam Ratulangi, 2018)
Languages have their own fashion for indicating the location of certain objects. Generally, such languages utilizes with morphemes such as ‘left’, ‘right’, ‘in front of’, and ‘in back of’, namely relative directions. However, there are also languages which utilizes cardinal directions, such as ‘north’, ‘south’, ‘west’ and ‘east’ for indicating the location of certain objects, namely absolute directions. In addition to cardinal directions, absolute directions also utilize uphill/downhill distinction in differentiating ‘up’ or ‘down’. Tontemboanese language is one of the languages which utilize absolute directions. This research aims to show how Tontemboanese speakers utter words in terms of spatial reference of the speakers. Through interview, it is revealed that Tontemboanese speakers utilize absolute directions to indicate the object locations, the motion of the actions, and parting phrases. In using the cardinal direction, the sun is the main source in indicating the directions.Keywords: absolute directions, Tontemboanese.